A method for testing the exchange current density of a lithium-ion electrode material
Patent Information
- Application Number
- CN202610924072.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]针对上述存在的问题,本发明的目的在于提供一种锂离子电极材料交换电流密度测试方法,解决现有技术无法消除浓差极化干扰,不能获得正、负极各自交换电流密度的问题
[0035]1. 本发明通过构建正极和负极对称电池,对称电池两个电极完全相同,施加微小扰动时两电极的过电位相互抵消,溶液中净浓度变化极小,从而将EIS信号纯净地聚焦于电极/电解液界面的电荷转移过程,显著提高了交换电流密度j0的测试准确性。
Smart Images

Figure CN122901504A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion electrode material testing technology, and in particular to a method for testing the exchange current density of lithium-ion electrode materials. Background Technology
[0002] The measurement of the exchange current density j0 of electrode materials is an indispensable core electrochemical testing method for the research, performance characterization, mechanism analysis, and industrial application of lithium-ion batteries (and other secondary batteries). Its core necessity lies in the fact that j0 is the only core parameter that can quantitatively characterize the intrinsic kinetic rate of electrode electrochemical reactions. It is directly related to the macroscopic electrochemical performance of electrode materials (such as rate performance, low-temperature performance, and cycle life) and microscopic reaction mechanisms. It can establish a precise correlation between "intrinsic performance - macroscopic performance - modification direction" for the research and optimization of electrode materials, and is also a key basis for distinguishing "kinetic limitations" from other performance limitations. Therefore, the j0 test solves the pain point of traditional macroscopic performance testing, which "can only show the results but cannot find the causes," and is an important bridge for realizing the transformation of electrode materials from basic research to engineering applications.
[0003] Currently, common methods for measuring exchange current density mainly include: First, the Tafel curve method and electrochemical impedance spectroscopy (EIS). These methods typically employ a lithium half-cell assembly with a positive / negative electrode. However, this half-cell structure suffers from severe concentration polarization interference, making it difficult to accurately reflect the intrinsic electrochemical reaction kinetics of the electrode material. Second, the rotating disk electrode (RDE) method. This method generates forced convection by rotating the electrode, theoretically eliminating concentration polarization completely and thus accurately characterizing the intrinsic electrochemical reaction kinetics of the electrode material. However, this method is not suitable for lithium battery materials already prepared as electrode sheets, as the electrode sheets cannot be rotated; its main application is limited to kinetic screening during the material synthesis stage.
[0004] Invention application No. 202510015050.5 discloses a method, apparatus, computer equipment, and computer-readable storage medium for measuring the exchange current density of a battery, relating to the field of battery testing technology. This application's solution determines the exchange current density of the battery under test based on the effective reaction area of the electrodes, the internal resistance of the battery under test, and the temperature of a preset environment, enabling rapid and accurate measurement of the battery's exchange current density. However, this solution also has drawbacks: it cannot obtain the exchange current density test results for the positive and negative electrodes separately; and it does not eliminate concentration polarization interference within the battery, meaning the test results are still affected by concentration polarization, and it cannot guarantee accurate acquisition of the intrinsic kinetic parameters of the electrode materials.
[0005] Therefore, there is a lack of existing technologies for a method that can effectively eliminate concentration polarization interference and is suitable for testing the exchange current density of positive and negative electrode materials in pre-formed lithium-ion battery electrode sheets. Summary of the Invention
[0006] To address the aforementioned problems, the present invention aims to provide a method for testing the exchange current density of lithium-ion electrode materials, thereby solving the problem that existing technologies cannot eliminate concentration polarization interference and cannot obtain the exchange current densities of the positive and negative electrodes.
[0007] The objective of this invention can be achieved through the following technical solution: a method for testing the exchange current density of lithium-ion electrode materials, comprising:
[0008] S1: Select lithium-ion battery cells with the same specifications and adjust the SOC of each battery cell to the target gradient.
[0009] S2: Disassemble each battery cell separately and collect the positive and negative electrode plates corresponding to each SOC gradient.
[0010] S3: Based on the collected positive and negative electrode plates, prepare positive and negative symmetrical cells with the same SOC gradient, and the corresponding half-cells.
[0011] S4: Perform EIS tests on the positive and negative symmetrical cells for each SOC gradient, and obtain the charge transfer impedance Rct by fitting.
[0012] S5: Perform CV tests on half-cells with different SOC gradients to obtain the active area S of the electrode material;
[0013] S6. Based on the charge transfer impedance Rct and active area S under each SOC gradient, calculate the exchange current density values of the positive and negative electrode materials under each SOC gradient.
[0014] The above steps enable separate testing of the exchange current density of the positive and negative electrode materials under different SOC states, solving the problems of traditional testing methods that cannot distinguish the exchange current density of the positive and negative electrodes and cannot obtain the variation law of exchange current density under different charging states. The test results can provide accurate parameter support for the construction of simulation models of lithium-ion batteries.
[0015] As a further embodiment of the present invention, the lithium-ion battery cells in S1 are of consistent specifications, including lithium-ion battery cells of the same batch, the same model and with good consistency in electrochemical performance.
[0016] As a further embodiment of the present invention, in S1, 11 lithium-ion battery cells with the same specifications are selected, and the SOC gradient of each battery cell is 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100%, covering the SOC range of the battery cells from 0% to 100%.
[0017] The consistent specifications of lithium-ion battery cells and the setting of SOC gradients ensure that the test covers the entire SOC range. Furthermore, the consistent initial state of all cells eliminates the interference of individual cell differences on the test results, ensuring that the subsequent changes in positive and negative electrode exchange current density under different SOCs are more accurate and reliable.
[0018] As a further embodiment of the present invention, the preparation of the positive electrode symmetric battery and the negative electrode symmetric battery includes:
[0019] The positive electrode sheet is cut into the size of a coin cell. The coin cell pack is assembled using a three-layer stacking method of one positive electrode sheet, one separator, and one positive electrode sheet with the same SOC gradient. Electrolyte is injected into the coin cell pack to obtain a positive symmetrical cell.
[0020] The negative electrode sheet is cut into the size of a coin cell. The coin cell pack is assembled using a three-layer stacking method of one negative electrode sheet, one separator, and one negative electrode sheet with the same SOC gradient. Electrolyte is injected into the coin cell pack to obtain a negative electrode symmetrical cell.
[0021] The fabrication of positive and negative symmetrical cells enables the testing of the electrochemical AC impedance of a single electrode under the same state of charge (SOC), without considering the influence of the other electrode on the test results. It allows for the direct measurement of the charge transfer resistance Rct of the positive and negative electrodes under different SOCs, which is beneficial for obtaining a complete understanding of the variation law of the exchange current density of the positive and negative electrodes under different SOC ranges.
[0022] As a further embodiment of the present invention, the EIS test parameters are set as follows: the voltage excitation signal amplitude is 5mV, the test frequency range is 1MHz~0.01Hz, and the battery temperature is kept stable during the test.
[0023] Reasonable parameter settings in EIS testing ensure that the testing process will not cause additional disturbances to the electrode reactions inside the battery. Under stable battery temperature, the test results can also eliminate resistance value deviations caused by temperature fluctuations, ensuring that the exchange current density calculated subsequently is more accurate.
[0024] As a further embodiment of the present invention, the CV test includes: performing CV tests on the electrode material under test at different scan rates within the non-Radida potential region of the half-cell; calculating the double-layer capacitance based on the linear relationship between the charging current and the scan rate; and then obtaining the active area S of the electrode material, expressed as:
[0025]
[0026] Where Ic is the charging current, ν is the scanning speed, Cdl is the double-layer capacitance, and Cdl is proportional to the active area S.
[0027] As a further embodiment of the present invention, the scanning speed ν may be 5mV / s, 10mV / s, 20mV / s, 50mV / s, 80mV / s or 100mV / s.
[0028] As a further embodiment of the present invention, the electrode material to be tested includes at least one of graphite, ternary materials, or lithium iron phosphate.
[0029] As a further embodiment of the present invention, the non-Radidatic potential region is: the voltage range of graphite relative to lithium metal is 0.1~0.3V, the voltage range of ternary materials relative to lithium metal is 3.0~3.8V, and the voltage range of lithium iron phosphate relative to lithium metal is 2.5~3.2V.
[0030] As a further embodiment of the present invention, the exchange current density value is expressed as:
[0031]
[0032] Where j0 is the exchange current density, R is the gas constant, T is the absolute temperature, F is the Faraday constant, n is the number of electrons transferred in the electrode reaction, Rct is the charge transfer impedance, and S is the active area of the electrode material.
[0033] The physical meaning of each parameter in the formula for the exchange current density is clear. Only the charge transfer impedance of the electrode reaction and the active area of the electrode material need to be measured. Combined with the known constants, the exchange current density can be calculated quickly. The calculation process does not require complex fitting, which reduces the difficulty of calculating the exchange current density.
[0034] The beneficial effects of this invention are:
[0035] 1. This invention constructs a symmetrical battery with a positive and negative electrode. The two electrodes of the symmetrical battery are identical. When a small perturbation is applied, the overpotentials of the two electrodes cancel each other out, and the net concentration change in the solution is minimal. This allows the EIS signal to be purely focused on the charge transfer process at the electrode / electrolyte interface, which significantly improves the accuracy of the exchange current density j0 test.
[0036] 2. This invention selects 11 battery cells and adjusts them to 11 SOC gradients (intervals of 10%) from 0% to 100%, assembling them into symmetrical batteries for testing. This allows us to obtain the exchange current density distribution of the positive and negative electrode materials throughout the entire state of charge range. This is of great significance for understanding the kinetic characteristics of materials at different charge and discharge stages and guiding battery design and optimization.
[0037] 3. This invention utilizes cyclic voltammetry (CV) at different scan rates in the non-Radida region to accurately calculate the double-layer capacitance Cdl using the linear relationship between charging current and scan rate, thereby converting it into the true active area S of the electrode material. This avoids the errors caused by directly using the geometric area, as the actual electrode surface is a porous and rough particle accumulation, and the actual reaction area is much larger than the geometric area. By normalizing the active area, the final calculated j0 better reflects the intrinsic kinetic characteristics of the material, eliminating the influence of process factors such as electrode thickness and compaction density.
[0038] 4. This invention adopts conventional button cell assembly and EIS / CV testing in combination. The operation process is standardized, the test parameters are clear, and the data processing is simple: EIS semicircle is fitted to extract Rct, CV data is linearly fitted to calculate Cdl, and then the data is substituted into the formula. No complex modeling or special equipment is required, which makes it easy to promote in the laboratory and production line.
[0039] 5. This invention uses battery cells of consistent specifications and employs measures such as disassembly in an argon glove box, electrolyte moisture ≤20ppm, constant temperature testing, and equilibration for 2.5h before EIS testing to ensure a temperature difference ≤0.1℃. These measures effectively reduce systematic and random errors, making the test results have good repeatability and comparability.
[0040] 6. The method of the present invention prepares positive electrode symmetrical cells and negative electrode symmetrical cells separately, and performs EIS testing and active area calibration separately. It can complete the exchange current density test of two materials, positive electrode and negative electrode, under the same method framework, and realizes the unification and efficiency of the test system. Attached Figure Description
[0041] Figure 1 This is a schematic flowchart of the method of the present invention;
[0042] Figure 2 The EIS diagrams of the symmetrical battery under different SOCs according to the method of the present invention are shown.
[0043] Figure 3 EIS diagrams of lithium iron phosphate under different SOCs according to the method of the present invention;
[0044] Figure 4 The CV diagrams of lithium iron phosphate materials at different scan rates according to the method of this invention are shown.
[0045] Figure 5 EIS diagrams of graphite under different SOCs according to the method of the present invention;
[0046] Figure 6 The image shows the CV curves of the graphite material at different scan rates according to the method of this invention. Detailed Implementation
[0047] Embodiments of the present invention are described in detail below. Examples of these embodiments are illustrated in the accompanying drawings, wherein the same or similar symbols denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0048] Example 1: As Figure 1 As shown, this embodiment discloses a method for testing the exchange current density of lithium-ion electrode materials, including the following steps:
[0049] S1: Select lithium-ion battery cells with the same specifications and adjust the SOC of each battery cell to the target gradient.
[0050] Prepare battery cells, for example, select 11 lithium-ion battery cells with the same specifications. The same specifications means that the lithium-ion battery cells are from the same batch, of the same model and have good electrochemical performance. This ensures that the basic test conditions are consistent and avoids interference with the final test results due to differences in the cells themselves.
[0051] Each cell's SOC was adjusted to 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100%, respectively, forming a 10% interval distribution gradient that covers the cell's SOC range of 0% to 100%.
[0052] Furthermore, the initial capacity deviation of the 11 cells is ≤2%, and the internal resistance deviation is ≤5%, to ensure sample consistency.
[0053] SOC adjustment adopts constant current and constant voltage (CC-CV) mode: when charging to the target SOC, first charge with a constant current of 0.2C to the corresponding voltage, then charge with a constant voltage of 0.02C until the current is ≤0.01C, and then let it stand in a constant temperature environment of 25±0.5℃ for 2 hours. The accuracy of SOC is verified by capacity backtracking method.
[0054] S2: Disassemble each battery cell separately and collect the positive and negative electrode plates corresponding to each SOC gradient.
[0055] Eleven cells with SOC adjusted to the target gradient were disassembled separately, avoiding damage to the electrodes during the disassembly process. The positive and negative electrodes corresponding to each SOC gradient were collected to obtain positive and negative electrode groups covering the 0%~100% SOC range.
[0056] Furthermore, the cell disassembly is carried out in a non-destructive manner to prevent the electrode sheets from being creased, shedding powder, or broken.
[0057] As a preferred embodiment, the electrode is disassembled in an argon-protected glove box (water and oxygen content ≤1ppm) using insulated ceramic tools (to avoid metal contamination).
[0058] The disassembly process includes: first, cutting the edges of the aluminum-plastic film and removing electrolyte residue, then separating the positive and negative electrode plates and the separator layer by layer, avoiding bending and scratching the electrode plates throughout the process.
[0059] S3: Based on the collected positive and negative electrode plates, prepare positive and negative symmetrical cells with the same SOC gradient, and the corresponding half-cells.
[0060] Each collected positive and negative electrode sheet is cut into the size of a button cell.
[0061] The preparation of a positive electrode symmetric cell includes: assembling a coin cell pack using a three-layer stacking method of one positive electrode, one separator, and one positive electrode with the same SOC gradient for positive electrode samples of various SOC gradients; then injecting an appropriate electrolyte into the coin cell pack to obtain a positive electrode symmetric cell; and allowing the encapsulated positive electrode symmetric cell to stand for 8 hours to ensure that the electrolyte fully wets the electrode and separator.
[0062] The preparation of the negative electrode symmetric cell includes: following the preparation process of the positive electrode symmetric cell described above, using negative electrode samples with different SOC gradients, to prepare coin-type negative electrode symmetric cells in the SOC range of 0%~100%, and then letting them stand for 8 hours to allow the electrolyte to fully impregnate them.
[0063] Furthermore, the separator is made of polypropylene, and the electrolyte is formulated with the same properties as the original battery cell, with a moisture content of ≤20ppm. The electrodes / separator / electrode are aligned and stacked in a glove box (deviation ≤0.2mm). The electrolyte is injected using a precision syringe, and the constant temperature chamber is maintained at 25±0.3℃, with the electrolyte set for 8 hours.
[0064] Electrode materials mainly include graphite, ternary and lithium iron phosphate materials.
[0065] A half-cell refers to a test cell consisting of a lithium metal sheet as a reference electrode and the electrode material under test (such as graphite, ternary and lithium iron phosphate materials). The potential of the lithium metal sheet is very stable, which can provide a fixed potential reference for the electrode material under test.
[0066] S4: Perform EIS tests on the positive and negative symmetrical cells for each SOC gradient, and obtain the charge transfer impedance Rct by fitting.
[0067] Electrochemical impedance spectroscopy (EIS) was performed on positive electrode symmetrical cells and negative electrode symmetrical cells at various SOC gradients. For example... Figure 2 , Figure 3 and Figure 5 As shown, the EIS test measures the impedance response of the symmetrical battery at different frequencies by applying a voltage excitation signal and then fitting the charge transfer impedance Rct. Table 1 shows the charge transfer impedance values of the lithium iron phosphate battery at different SOC gradients obtained by the test.
[0068] Table 1: Charge transfer impedance values of lithium iron phosphate at different SOC gradients
[0069]
[0070] Furthermore, electrochemical impedance spectroscopy (EIS) testing can be performed with the following parameters: voltage excitation signal amplitude of 5mV, test frequency range of 1MHz to 0.01Hz, and battery temperature kept stable during the test.
[0071] Furthermore, before testing, the symmetrical cells were placed in a constant temperature shielded box at 25±0.2℃ for equilibration for 2.5 hours to ensure that the temperature difference between the cells and the ambient temperature was ≤0.1℃. A high-precision electrochemical workstation (impedance test accuracy ±0.1%) was selected, and the excitation signal was a sinusoidal AC signal (amplitude 5mV, no DC bias).
[0072] S5: Cyclic voltammetry tests are performed on half-cells with different SOC gradients to obtain the active area S of the electrode material.
[0073] Cyclic voltammetry (CV) testing primarily targets graphite, ternary, and lithium iron phosphate electrode materials. The scanning regions during testing are: 2.5-3.2V for lithium iron phosphate and 3.0-3.8V for ternary materials in the non-Radicarboytic potential region, and 2.5-3.2V for lithium iron phosphate. In the non-Radicarboytic potential region without redox reactions, the electrode current is solely contributed by the charging and discharging of the electric double layer. The charging current (Ic) exhibits a linear relationship with the scan rate (ν), expressed as:
[0074] Ic = ν × Cdl
[0075] Where Cdl is the double-layer capacitance, which is proportional to the active area S, and ν is the scan rate, such as Figure 4 and Figure 6 As shown, CV tests were performed on lithium iron phosphate and graphite materials at scan rates of 5mV / s, 10mV / s, 20mV / s, 50mV / s, or 100mV / s, respectively, and the active area S of each material was calculated according to the formula.
[0076] S6. Based on the charge transfer impedance Rct and active area S under each SOC gradient, calculate the exchange current density values of the positive and negative electrode materials under each SOC gradient.
[0077] Based on electrochemical principles, the exchange current density is calculated using the following formula for each SOC gradient for the positive and negative electrode materials:
[0078]
[0079] For example, the calculated exchange current density values of lithium iron phosphate at different SOCs are shown in Table 2:
[0080] Table 2: Exchange current density values of lithium iron phosphate under different SOC gradients
[0081]
[0082] j0 is the exchange current density (in A·cm⁻²); R is the gas constant, with a value of 8.314 J·mol⁻¹·K⁻¹; T is the absolute temperature (in K), which is the thermodynamic temperature of the test environment; F is the Faraday constant, with a value of 96485 C·mol⁻¹; n is the number of electrons transferred in the electrode reaction, and the insertion and extraction reactions of Li⁺ in lithium-ion batteries all satisfy n=1; Rct is the charge transfer impedance (in Ω·cm²), obtained by fitting the EIS test results; S is the active area of the electrode material (in cm²), which is the actual active area area of the electrode sample.
[0083] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for testing the exchange current density of lithium-ion electrode materials, characterized in that, include: S1: Select lithium-ion battery cells with the same specifications and adjust the SOC of each battery cell to the target gradient. S2: Disassemble each battery cell separately and collect the positive and negative electrode plates corresponding to each SOC gradient. S3: Based on the collected positive and negative electrode plates, prepare positive and negative symmetrical cells with the same SOC gradient, and the corresponding half-cells. S4: Perform EIS tests on the positive and negative symmetrical cells for each SOC gradient, and obtain the charge transfer impedance Rct by fitting. S5: Perform CV tests on half-cells with different SOC gradients to obtain the active area S of the electrode material; S6. Based on the charge transfer impedance Rct and active area S under each SOC gradient, calculate the exchange current density values of the positive and negative electrode materials under each SOC gradient.
2. The method for testing the exchange current density of lithium-ion electrode materials according to claim 1, characterized in that, In S1, 11 lithium-ion battery cells with the same specifications are selected. The SOC gradient of each battery cell is 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100%, covering the SOC range of the battery cells from 0% to 100%.
3. The method for testing the exchange current density of lithium-ion electrode materials according to claim 2, characterized in that, The lithium-ion battery cells in S1 are of the same specifications, including that they are from the same batch, of the same model, and have good electrochemical performance.
4. The method for testing the exchange current density of lithium-ion electrode materials according to claim 1, characterized in that, The preparation of the positive electrode symmetrical battery and the negative electrode symmetrical battery includes: The positive electrode sheet is cut into the size of a coin cell. The coin cell pack is assembled using a three-layer stacking method of one positive electrode sheet, one separator, and one positive electrode sheet with the same SOC gradient. Electrolyte is injected into the coin cell pack to obtain a positive symmetrical cell. The negative electrode sheet is cut into the size of a coin cell. The coin cell pack is assembled using a three-layer stacking method of one negative electrode sheet, one separator, and one negative electrode sheet with the same SOC gradient. Electrolyte is injected into the coin cell pack to obtain a negative electrode symmetrical cell.
5. The method for testing the exchange current density of lithium-ion electrode materials according to claim 1, characterized in that, The EIS test parameters are set as follows: The voltage excitation signal amplitude is 5mV, the test frequency range is 1MHz~0.01Hz, and the battery temperature is kept stable during the test.
6. The method for testing the exchange current density of lithium-ion electrode materials according to claim 1, characterized in that, The CV test includes: CV tests were performed on the electrode material under test at different scan rates within the non-Radida potential region of the half-cell. The double-layer capacitance was calculated based on the linear relationship between the charging current and the scan rate, and the active area S of the electrode material was obtained, expressed as: Where Ic is the charging current, ν is the scanning speed, Cdl is the double-layer capacitance, and Cdl is proportional to the active area S.
7. The method for testing the exchange current density of lithium-ion electrode materials according to claim 6, characterized in that, The scanning speed ν can be 5mV / s, 10mV / s, 20mV / s, 50mV / s, 80mV / s, or 100mV / s.
8. The method for testing the exchange current density of lithium-ion electrode materials according to claim 6, characterized in that, The electrode material to be tested includes at least one of graphite, ternary materials, or lithium iron phosphate.
9. The method for testing the exchange current density of a lithium-ion electrode material according to claim 6, characterized in that, The non-Radidatic potential regions are: 0.1~0.3V for graphite relative to lithium metal, 3.0~3.8V for ternary materials relative to lithium metal, and 2.5~3.2V for lithium iron phosphate relative to lithium metal.
10. The method for testing the exchange current density of a lithium-ion electrode material according to claim 6, characterized in that, The exchange current density value is expressed as: Where j0 is the exchange current density, R is the gas constant, T is the absolute temperature, F is the Faraday constant, n is the number of electrons transferred in the electrode reaction, Rct is the charge transfer impedance, and S is the active area of the electrode material.
Citation Information
Patent Citations
Method and device for measuring battery exchange current density, computer equipment and medium
CN119881700A